Two cases of autosomal recessive woolly hair with LIPH gene mutations. (17th April 2013) - Harada, Kazutoshi; Inozume, Takashi; Kawamura, Tatsuyoshi; Shibagaki, Naotaka; Kinoshita, Tomoko; Deguchi, Nobuhiro; Shimada, Shinji
Abstract Background Woolly hair is a hereditary disorder characterized by fine and tightly curled hair. Autosomal recessive woolly hair (ARWH) was recently determined to result from mutations in either the lipase H (LIPH) or the LPAR6 (P2RY5) gene. Case report An 8‐year‐old boy (proband) and his 11‐year‐old brother presented with tightly coiled and sparse scalp hair. The boys did not have cardiomyopathy, palmoplantar keratoderma, or facial dysmorphism. Their parents had normal hair growth and no woolly hair. The sequence analysis of their genomic DNA revealed that the proband and his brother had a homozygous mutation of c.736T > A in the LIPH gene. On the basis of these findings, these patients were diagnosed with ARWH. Conclusions To the best of our knowledge, only 20 cases of ARWH have been previously reported in Japan. However, several reports showed that one mutation was detected in the 4/200 normal and unrelated alleles in healthy Japanese control individuals, indicating the presence of ARWH in patients with extremely mild symptoms.